Comparision of Percutaneous Nephrolithotomy and Retrograde Intrarenal Surgery For The Treatment of Multicalyceal and Multiple Renal Stones - Demirbas, Arif; Yazar, Veli Mert; Ersoy, Erim; Demir, Demirhan Orsan; Ozcan, Serkan; Karakan, Tolga; Doluoglu, Omer Gokhan; Resorlu, Berkan; Hascicek, Ahmet Metin; Gunseren, Kadir Omur (Urology Journal, 2018)
Purpose: Comparison of efficiency and reliability of percutaneous nephrolithotomy (PNL) and retrograde intrarenal surgery (RIRS) in treatment of multicalyceal and multiple renal stones in the same renal unit. Materials and Methods: Between 2011 and 2015, records of patients who underwent surgery for renal stone were retrospectively reviewed. Patients who had multiple stones located in different calices in the same renal unit were included. The patients that underwent PNL and RIRS were defined as Group I and Group II, respectively. Patient criteria (age,sex); the stone characteristics; time of procedure, fluoroscopy and hospitalization; stone-free and complication rates of groups were evaluated between the treatment groups. Result: There were no significant differences in terms of age, gender, BMI, laterality, number of stones, number of stone localization, hounsfield units and surface area characteristics of the stone between the PNL (n = 47) and RIRS (n = 35) groups (P = .558, P = .278, P = .375, P = 0.051, P = .053, P = .064, P = .642, P = .080, respectively). Stone free rate was 59.6% (n=28) in PNL, and 88.6% (n=31) in RIRS (P=.004). 1st or 2nd degree complications according to Modified Clavien Classification developed in 10 patients (21.3%) in Group I and 1 patient (2.9%) in Group II (P = .015). The 3A or 3B complications were similar in groups (P = .077). Time of procedure, fluoroscopy and hospitalization were significantly lower in Group II (P < .001, P < .001 and P < .001, respectively). Conclusion: RIRS is more effective and more reliable procedure than PNL with higher stone-free and lower complication rates in treatment of multicalyceal and multiple stone in the same renal unit.